Analisis Pengaruh Subtitusi Tepung Daun Katuk dan Tepung Ubi Jalar Kuning sebagai Alternatif Camilan Tinggi Serat dan Rendah Lemak untuk Remaja Obesitas - Wafidatul Itsna Mukholidah; Dian Ayu Ainun Nafies (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
Adolescent obesity is a health problem that arises due to an imbalance between energy intake and expenditure, one of which is influenced by a diet high in fat and low in fiber. This condition needs attention because it has an impact on the risk of chronic diseases in adulthood. This study aims to analyze the effect of substitution of katuk leaf flour and yellow sweet potato flour on the nutritional content and acceptability of muffins as a healthier alternative to high-fiber and low-fat snacks for adolescents. This laboratory's experimental research used a Complete Random Design (RAL) with four formulations (P0, P1, P2, P3). The analysis carried out included a proximate test to determine the nutritional content and an organoleptic test to assess the level of acceptance of panelists. The results of the study show that the substitution of katuk leaf flour and yellow sweet potato flour can increase fiber content and significantly reduce fat content. The best formulation is found in P2 with the highest level of preference. Thus, the use of these two types of flour has been proven to be able to improve the nutritional quality of muffins without reducing the acceptance of panelists, so that it has the potential to be a nutritious snack choice for teenagers.